Discriminatory Capacity of Obesity Indicators as Predictors of High Liver Fat in Us Adolescents - Garcia-Hermoso, A (John Wiley and Sons Inc, 2022)
Background: The aims of this study were to assess the potential of 16 anthropometric, body composition and endocrine indexes as predictors of high liver fat and determine the most appropriate cut-off points in US adolescents. Methods: A cross-sectional study was conducted on a population of 816 adolescents aged 12-17 years. The FibroScan®502V2 device was used to estimate the controlled attenuation parameter (CAP). Body fat percentage, fat mass, trunk fat percentage and trunk fat mass were measured by dual-energy X-ray absorptiometry. Anthropometric data and metabolic parameters were determined. Receiver operating characteristic curves were analysed to estimate the optimal cut-off points that best identify adolescents with high liver fat (CAP ≥90th percentile). Results: In boys, triponderal mass index (TMI) had the highest area under curve (AUC) value (0.865) and the optimal cut-off score for TMI was 17.47 kg/m3, which had 81.32 sensitivity and 82.99 specificity. In girls, trunk fat index (TFI) had the highest AUC value (0.826) and its optimal cut-off score in screening for high liver fat was 3.76 kg/m2, which had 74.04 sensitivity and 88.03 specificity. Fat mass index (FMI) index had the second highest AUC values (0.863 in boys 0.812 in girls) in both sex; the cut-off point for the detection of high liver fat was <8.66 kg/m2 for girls and <7.45 kg/m2 for boys. Conclusion: Assessment of TMI in boys, TFI in girls, and FMI in both sexes are low-cost and easy-to-use parameters that may be useful as early screening tools for possible high liver fat in adolescents. © 2021 Stichting European Society for Clinical Investigation Journal Foundation. Published by John Wiley & Sons Ltd.